Regulasi Pendirian Rumah Ibadat di Indonesia: Tinjauan Asas-asas Pembentukan Hukum - Sinaga, Budiman N.P.D; Siregar, Hisar; Raymando, Samuel; Sitepu, Desy Febrina (Journal of Education, Humaniora and Social Sciences (JEHSS), 2024)
This article aims to explain the causes of many laws and regulations regarding the establishment of houses of worship that cannot be implemented. Until now there are still people who reject the establishment of synagogues. Through research, we want to know the principles of the formation of laws and regulations and evaluation of the law on the establishment of houses of worship in Indonesia.Â  The results of the research can be used for the formation of laws on the establishment of better houses of worship. The sources of legal research used are primary and secondary legal materials. Primary legal materials include legislation and court decisions. Secondary legal materials include books, journals, legal dictionaries, as well as commentaries on court decisions. Research sources were collected in the city of Medan. From this research, it can be seen that the laws and regulations regarding the establishment of houses of worship have not paid attention to all the principles of the formation of laws and regulations. In the future, the formation of laws and regulations on the establishment of houses of worship must take into account all the principles of the formation of laws and regulations without exception